2015
DOI: 10.29047/01225383.21
|View full text |Cite
|
Sign up to set email alerts
|

Operating conditions influence on VMD and SGMD for ethanol recovery from aqueous solutions

Abstract: This work focuses on Vacuum Membrane Distillation (VMD) and Sweeping Gas Membrane Distillation (SGMD) as a separating technique of ethanol from aqueous solutions. VMD was studied at moderate temperature (30, 40 and 50°C) and pressure (0.11, 0.20 and 0.30 atm) conditions, whereas SGMD was studied at different temperatures (50 and 70°C) and air-flow rates (10x10 -6 and 20x10 -6 m 3. min -1 ). These techniques were experimentally studied using prepared ethanol-water solutions and fermented broths, with ethanol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The influence of several operating variables on the SGMD processes has been previously investigated [6,7]. The temperatures of the feed and sweeping phases have been identified as the most relevant process conditions; in particular, the temperature difference between the two phases must be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of several operating variables on the SGMD processes has been previously investigated [6,7]. The temperatures of the feed and sweeping phases have been identified as the most relevant process conditions; in particular, the temperature difference between the two phases must be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Among the four setups in MD, VMD and SGMD draw more attention as ethanol separation methods, since both allow for a higher flux of the permeate with a decent concentration of alcohol [6][7][8][9]. From the literature, it was found that only a few studies have been carried out on the MD process applied to recover alcohols (mostly ethanol).…”
Section: Introductionmentioning
confidence: 99%
“…Gryta et al [11] investigated a range of ethanol concentrations in a fermentation medium and concluded that the selectivity depends on the feed temperature; indeed, increasing from 30 • C to 60 • C, the enrichment factor varied from 4 to 6. Cotamo-De La Espriella et al [7] analyzed and compared two configurations, VMD and SGMD, using prepared water-ethanol solutions and water-ethanol mixtures from fermented broths. At first, they considered working under moderate vacuum conditions for VMD, using membranes with a pore diameter up to 5 µm for SGMD; this was the first study reporting the comparison of the two techniques under similar operating conditions.…”
Section: Introductionmentioning
confidence: 99%